Investigating Epidemiology of Trauma caused by Traffic Accidents and Relief Operation by EMS Personnel in Valiasr Teaching Hospital in Southwestern of Iran - Bijani, Mostafa; Khaleghi , Ali Asghar; Zare, Somayeh; Amirfakhraei, Azita; Rostami, Khatereh; Eslami, Jamshid; Ghasemi, Afsaneh (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Mortality, injuries, and disabilities caused by the traffic accidents are among the important challenges affecting the health of society, so that the traffic accidents are the most important cause of the death, disability, and hospitalization with significant economic and social consequences. The objective of this study was to evaluate the causes and frequency of the trauma caused by the traffic accidents and relief operation by the EMS (Emergency Medical Service) personnel of Valiasr teaching hospitals in Fars province in the southwestern of Iran in 2019. Methodology: This was a descriptive-analytical study in which all victims who were transferred to hospital during the year 2018 were studied. Checklist and medical records of the patients were used to collect the data. The data were analyzed by SPSS-22 software and descriptive statistics and independent t-test. Results: 65% of the subjects were male and 35% of them were female. Independent t-test showed a significant relationship between the sex and frequency of the traffic accidents, so that its rate was higher in the males than that in females (P <0.001). In terms of age group, most accidents occurred in the age group of 25-19 years old. Head trauma and spinal cord injuries were the leading cause of the death among the victims. Sixty percent of the victims had been transferred to the medical centers by the EMS personnel and the cervical and lumbar spines immobilization was well done by the personnel. Forty percent of the victims were transferred to the hospital by the personal vehicle. The highest number of the deaths occurred at the accident site. Conclusion: As the age group of below 30 years old was the highest age group in the traffic accidents, it is necessary to take necessary steps in the area of education and development of culture in the use of the vehicles and observing the driving rules.